China's marine manufacturing export growth: Policy, status, and driving components. (March 2023) - Feng, Fan; Zhai, Chenqi; Yang, Zhenguo; Feng, Kuo
Abstract: This paper is the first to quantify the evolution of the scale, structure, and competitiveness of China's marine manufacturing exports based on a product-level database. The results show that although the scale of China's marine exports increased rapidly between 2002 and 2010, it slowed down after 2010. Meanwhile, the shipbuilding industry has always occupied the leading position in marine manufacturing exports, but export competitiveness has experienced a significant developmental bottleneck in recent years. Moreover, by decomposing the intrinsic driving factors of marine manufacturing exports, we find that only the scale effect promoted the export of marine products. China has not effectively developed marine manufacturing exports due to the domination of traditional industries, low technology conversion, and insufficient policy support. Therefore, we put forward relevant policy suggestions and countermeasures to address the weak exports of China's marine industry.